Accurate and Rapid Protein Concentration Measurement of In‐Process, High Concentration Protein Pools. (21st September 2018) - McKechnie, William S.; Tugcu, Nihal; Kandula, Sunitha
Abstract : Protein concentration is a critical product quality attribute and required for any therapeutic protein. Many commercial and investigational new biologics are now formulated at high concentrations (>100 mg/ml) to achieve successful subcutaneous administration. Assaying protein concentration in high concentration formulations poses a challenge, as traditional absorption spectroscopy and UPLC/HPLC (ultra/high performance liquid chromatography) assays cannot accurately measure such high concentrations without further solution manipulation. However, recent advances in UV/vis technology have led to the creation of instruments that measure samples at relatively short (<1 cm) path lengths, which would allow them to accurately measure high concentration protein samples in accordance with Beer Lambert Law principles. In this research, samples of five different proteins at concentrations ranging from 0.15 to 242 mg/ml (corresponding to OD280 vales of 0.15–315 AU) were measured on two different instruments employing different techniques of low path length UV/vis measurements. In order for the techniques to meet MSD's acceptance criteria for release assays, measurements were required to be accurate to within 10% of a reference measurement (performed on a traditional UV/vis spectrophotometer) and to be precise within 5% CV. The results show that using a technique known as slope spectroscopy, it is possible to measure OD280 from 0.5 to 315 AU with <7% error relative to the reference measurement. If instead measurements are taken using an instrument utilizing a single, small path length, it is possible to measure absorbances from 0.2 to ~75 AU with <7% error. This article concludes that the slope spectroscopy technique performed within the acceptance criteria across the full range of measured absorbances and that the single, short path length measurement performed within the acceptance criteria up to 75 AU.